If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20(-3 + 2x) = (4x) * 5 (-3 * 20 + 2x * 20) = (4x) * 5 (-60 + 40x) = (4x) * 5 Remove parenthesis around (4x) -60 + 40x = 4x * 5 Reorder the terms for easier multiplication: -60 + 40x = 4 * 5x Multiply 4 * 5 -60 + 40x = 20x Solving -60 + 40x = 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. -60 + 40x + -20x = 20x + -20x Combine like terms: 40x + -20x = 20x -60 + 20x = 20x + -20x Combine like terms: 20x + -20x = 0 -60 + 20x = 0 Add '60' to each side of the equation. -60 + 60 + 20x = 0 + 60 Combine like terms: -60 + 60 = 0 0 + 20x = 0 + 60 20x = 0 + 60 Combine like terms: 0 + 60 = 60 20x = 60 Divide each side by '20'. x = 3 Simplifying x = 3
| 10ac-x=3 | | 8(x+6)+x=2(x+2)+7 | | -8(-2x+5)=-136 | | 2(-10-7x)=50 | | 2(5-1.7b)=15.1-7(1.7) | | 2v-3v+3-4v=0 | | (3x-5)(x-8)=0 | | 11+6y-8y=-3+3y | | 13x-4=7x-22 | | 48-32=4(12-x) | | -2gh(g^3h^5)=0 | | 7x+2=4x-9 | | 8b-8=-6(b-3)+6(1+2b) | | 12x-14=16x | | -(1+7x)-6(-7-x)=6 | | 7n-8+2+7n=0 | | -4(2+m)=2(m-7) | | 60y-108+12= | | Q+2=q+16 | | 12=1/3z+7 | | -4y^3-8xy^4=4y^3(1+2xy) | | 4y=5x+4 | | X-32=4(12-y) | | -6+4s=-2 | | 2u+4=16 | | 2(7x+3)=20 | | -2x+8x-7=6(x-4)-3 | | 0=3x^2-x-120 | | -6v+3v-9=-3 | | 4z+6=2z+6 | | -9=7(7v+8)+4(5v+1) | | 3(a-1)-5=34 |